Violent Rationality: Police Violence as Instrumental Reason - Joubert, Paul (The Stellenbosch Socratic Journal, 2022)
Amidst the seemingly rapidly increasing international prevalence of police violence against black people, many have begun questioning the institution of policing and the rationale behind its existence. This public consciousness of police violence might be a new development in recent history, but many scholars have investigated policing and racism through the lens of a critical theory of race. This paper will analyse the mode of rationality supporting police violence among the perpetrators, identifying it as instrumental reason as described by Horkheimer and Adorno. The concept of instrumental reason will be discussed in the context of the Frankfurt School, after which police violence will be described in general, and connections between the theory and real-world examples will be drawn. The theoretical analysis will be used to attempt to provide insight into the function of police rationality. It will be shown, using the theoretical tools from the theory of instrumental reason, the manner in which the institution of policing utilises instrumental reason in order to subjugate humans — particularly black people — to an inscrutable end.